INTERESTING FEATURES OF FEMALE DROMEDARY (CAMELUS DROMEDARIUS) REPRODUCTION - PUROHIT, G N; VYAS, SUMANT; SARSWAT, CHANDRASHEKHER; KUMAR, AMIT; DHOLPURIA, SANDEEP (The Indian Journal of Animal Reproduction, 2023)
Inormation on the reproduction in camel continues to be poorly known and scattered. Some interesting featuresinclude seasonality of breeding, delayed puberty, peculiar anatomy of the reproductive structures, poorly definedestrus and estrous cycle and induced nature of the ovulation. Other interesting features include exclusive left uterinehorn pregnancy, faster demise of the corpus luteum in the absence of pregnancy, an early maternal recognition ofpregnancy, upward curling of tail (tail cocking) by Day 15 of pregnancy, diffuse placenta and a longer gestation periodof 12-13 months. This review collates scientific data on the above interesting features of female camel reproduction.
Keywords: Camel; Endocrinology; Estrus; Physiology; Pregnancy; Parturition